2022
DOI: 10.1186/s41256-022-00257-z
|View full text |Cite
|
Sign up to set email alerts
|

The direct and indirect impact of COVID-19 pandemic on maternal and child health services in Africa: a scoping review

Abstract: Introduction The novel coronavirus disease 2019 (COVID-19) continues to disrupt the availability and utilization of routine and emergency health care services, with differing impacts in jurisdictions across the world. In this scoping review, we set out to synthesize documentation of the direct and indirect effect of the pandemic, and national responses to it, on maternal, newborn and child health (MNCH) in Africa. Methods A scoping review was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…While these initial studies were pivotal in reporting early pandemic trends, the longer term societal impacts of COVID-19, including rising poverty3 16 and interruptions to schooling and employment,17 were likely to affect relationships and childbearing decisions 18 19. At the same time, growing economic disparities were projected to affect people’s financial access and use of health services,4 20 potentially reducing their ability to achieve their reproductive goals. Furthermore, early impact estimates were drawn from phone-based surveys amid COVID-19 lockdowns, which may have affected the interpretation of early study findings due to selection bias and data collection mode 14 15 21.…”
Section: Introductionmentioning
confidence: 99%
“…While these initial studies were pivotal in reporting early pandemic trends, the longer term societal impacts of COVID-19, including rising poverty3 16 and interruptions to schooling and employment,17 were likely to affect relationships and childbearing decisions 18 19. At the same time, growing economic disparities were projected to affect people’s financial access and use of health services,4 20 potentially reducing their ability to achieve their reproductive goals. Furthermore, early impact estimates were drawn from phone-based surveys amid COVID-19 lockdowns, which may have affected the interpretation of early study findings due to selection bias and data collection mode 14 15 21.…”
Section: Introductionmentioning
confidence: 99%
“…Service provision shifted dramatically to accommodate the need for COVID-19 treatment and prevention efforts, at times at the expense of essential SRH services. This finding is reflected in other research as well; a scoping review of studies from across Africa found disruptions in maternal and child health service provision were a common theme in countries including South Africa and Kenya as well [ 9 ]. Declines in utilization of sexual and reproductive health services in the early months of the pandemic have been documented in numerous countries, such as Nigeria, South Africa, and Pakistan [ 32 , 33 ], as well as prior research in Ethiopia [ 12 , 24 ].…”
Section: Discussionmentioning
confidence: 69%
“…At the same time, efforts to mitigate the spread of COVID-19, such as travel restrictions and changes to health service delivery, have impacted the availability of SRH services, and subsequently SRH outcomes [ 8 ]. In a scoping review of research from across Africa, 78% of studies reported delayed or decreased access to maternal and child health services due to the pandemic [ 9 ]. Subsequently, preference for home birth increased, health facility visits and inpatient care decreased, and health system capacity was reduced, with added challenges faced by already vulnerable populations such as adolescents and displaced people [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we found no evidence of this, there was an increase in the number who were not risk-strati ed. This could be due to several reasons, for example reduced senior clinical oversight due to the increased work demands and reduced sta ng associated with the pandemic waves [19], the junior HCPs may have lacked the con dence to accurately stratify each neonate. Alongside this the time pressure to admit and discharge neonates may have meant the information to accurately stratify the HIV-exposed neonates may not have been available or accurately recorded.…”
Section: Discussionmentioning
confidence: 99%